Aktualisasi Diri Siswa dalam Proses Pembelajaran Pendidikan Agama Kristen dan Budi Pekerti Berdasarkan Perspektif Carl R. Rogers - Lesilolo, Herly Janet (Guidance and Counseling Study Program, Pattimura University, 2017)
This study aims to examine the application of self-actualization of students according to Carl, R. Rogers in the teaching and learning process of Christian Religious Education and Character Based on the curriculum 2013. Background of research problem is the teaching and learning process of Christian Education and Character Budi Pekerti Based on the 2013 curriculum in the fourth grade of school Basic has not developed self-actualization of students. Teachers have not helped students develop themselves, know themselves as unique human beings and help students realize the potentials that exist within students. As a result students are not critical and sensitive to social reality and have not been able to direct themselves in solving a problem. The objectives of the research are: (1) to describe the way of learning of students who self-actualize in teaching and learning process of PAK and morality based on curriculum 2013, (2) to describe the role of teacher so that students can mengatualisasikan self-learning process of PAK and Budi Pekerti based on curriculum 2013, 3) describe the teaching and learning process of PAK and Budi Pekerti based on the 2013 curriculum that self-actualizes students. The results showed, (1) Students become active learners, students develop thinking skills, communicate, act, and be virtuous; Students seek answers with their own student efforts based on correct facts; Students and teachers show the mutual relationships meet the needs because teachers and students have different roles in the PBM. (2) Teachers are not patronizing, teachers build trust between students and teachers, students with students, teachers invite students to participate, teachers do not patronize, do not restrict students looking and finding, independent of other students pouring ideas. (3) The learning process from the students 'experience, whether cognitive, attitudes, or skills, develops students' courage and skills, active interactional relationships include active communication, media utilization and social relationships so that teachers and students are free to ask or respond to questions or opinions.